Out-migration and Returnee Migrants’ Integration in Farm Production: A Case Study from Andhikhola Rural Municipality - Rijal, Shiba Prasad; Paudel, Devi Prasad (Interdisciplinary Research in Education, 2024)
This paper aims to analyze the volume of out-migration and returnee migrants’ integration in farm production focusing on the case of Andhikhola Rural Municipality. Necessary data/information were collected from 364 randomly selected households with six group discussions and 12 key informants’ interviews. Collected data were processed using SPSS programs and qualitative techniques. The study reveals that people from this area have migrated to different destinations for better jobs and opportunities. Altogether 234 persons migrated to various destinations abroad while 185 persons migrated to other parts of Nepal. The out-migration of the population is on the rise and increase in some years to come. Likewise, 109 persons returned home due to the COVID-19 pandemic and other reasons. Returnee migrants have started translating experiences and skills gained abroad with financial earnings into productive farm enterprises. The study shows that returnee migrants. This can change traditional agricultural practices and production. The government should encourage them by providing financial and technical support.